Q: 2x2 5x -2

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

First you should combine equal terms. For example, 2x2 and -4x2 can be combined as -2x2. Then you can use the quadratic formula.Additonal Answer:-2x2+5x+3-4x2+22 = 0Collect like terms: -2x2+5x+25 = 0Divide al terms by -1: 2x2-5x-25 = 0Factorise: (2x+5)(x-5) = 0Solutions are: x = -5/2 or x = 5

Discriminant = 52 - 4 x 2 x (-8) = 89

5X + 2X + 7 when X=2 Replace X with 2 (5x2) + (2x2) +7 Work parenthesis first 7 + 4 + 7 Answer 7 + 4 + 7 = 18

x2 plus 6x-2 equal -2x2 plus x ..=7x equal -3x2 ..4x=2x=2 answer ..check it if u dont want to trust ..Improved Answer:x2+6x-2 = -2x2+xx2+2x2+6x-x-2 = 03x2+5x-2 = 0(3x-1)(x+2) = 0x = 1/3 or x = -2The answer can be checked by using the quadratic equation formula.

((15xy2)/(x2+5x+6))/((5x2y)/(2x2+7x+3)) =(15xy2/5x2y)*(2x2+7x+3)/(x2+5x+6) =(3y/x)*(((2x+1)(x+3))/((x+2)(x+3) =(3y(2x+1))/(x(x+2)) =(6xy+3y)/(x2+2x)

Related questions

2x2-2 = -5x-1 2x2+5x-2+1 = 0 2x2+5x-1 = 0 Use the quadratic equation formula to find the values of x: x = 0.1861406616 or x = -2.686140662

2x2 + (5x-4x)2 + (x-x)2 = 2x2 + x2 + 02 = 2x2 + x2 = 3x2

(x - 2)(2x + 9)

You would first factor out anything that is common between the 3 parts. 2x2 is the greatest common factor. To pull out the 2x2, you divide each term by 2x2 like so:12x4/2x2=6x210x3/2x2=5x-12x2/2x2=-6We now know that 12x4+10x3-12x2= 2x2(6x2+5x-6)The next step involves using the "slip and slide" method for the trinomial inside the parentheses:6x2+5x-6x2+5x-36(x+9)(x-4)(x+9/6)(x-4/6)(x+3/2)(x-2/3)(2x+3)(3x-2)Remembering that the result for the slip and slide method only accounts for 6x2+5x-6 we must multiply (2x+3)(3x-2) by 2x2.Your final answer is 2x2(2x+3)(3x-2).

2x2+5x-3 = 0 (2x-1)(x+3) = 0 x = 1/2 or x -3

Provided that x- 2 is not zero: 2x3 + x2 - 13x + 6 = 2x3 - 4x2 + 5x2 - 10x - 3x + 6 = 2x2*(x - 2) + 5x*(x - 2) - 3*(x - 2) = (x - 2)*(2x2 + 5x - 3) Therefore, (2x3 + x2 - 13x + 6)/(x - 2) = (x - 2)*(2x2 + 5x - 3)/(x - 2) = 2x2 + 5x - 3 If x = 2 so that x - 2 = 0, then the expression is not defined.

2x2 - 5x + 6 = ?x = -1(2 x (-1)2) - (5 x -1) + 6 = ?(2 x 1) - (-5) + 6 = ?2 + 5 + 6 = 13

I messed up the question I ment what are the solutions to 2x^2 + 5x + 8 = 6

First you should combine equal terms. For example, 2x2 and -4x2 can be combined as -2x2. Then you can use the quadratic formula.Additonal Answer:-2x2+5x+3-4x2+22 = 0Collect like terms: -2x2+5x+25 = 0Divide al terms by -1: 2x2-5x-25 = 0Factorise: (2x+5)(x-5) = 0Solutions are: x = -5/2 or x = 5

It is: 3x2-5x-2 = 0 and the value of x is -1/3 or 2 when solved

2x3 - 5x2 + 5x - 2 = x(2x2-5x+3) + 2x - 2 = x(2x-3)(x-1) + 2(x-1) = (x-1)[x(2x-3)+2] = (x-1)(2x2-3x+2) I did it by trial and error, through experience -- no set procedure. (2x2-3x+2) cannot be factored, which is evidenced by calculating (b2-4ac), where a = 2; b=-3; and c=2 from the expression (2x2-3x+2). (b2-4ac) = (9-16) = -7, which has no real square root value. That is, sqrt(-7) is an imaginary number. ========================

After long division, (2x2-5x+5)/(x-2) = 2x-1+3/(x-2).